Actividad con escritores. (UNED, 2025)
Mesa principal, grupo mediano de personas con José Joaquín Calvo, Régulo Solís, Guido Miranda, Adelita Sibaja, Eugenio Rodríguez, Rodrigo Arias, Alberto Cañas, Luis Ferrero, Rodrigo Alberto Carazo Zeledón